Parental Knowledge, Attitude, and Practice towards Dental Care Visits for Children 6-12 Years of Age during the Covid-19 Pandemic Period - Octiara, Essie; Rizky, Agneschita (Dentika: Dental Journal, 2023)
Covid-19 is an infectious disease that is growing rapidly throughout the world. Dental care carries a risk of infection, as the procedure involves face-to-face communication with the patient, exposure to saliva, blood, other body fluids and the use of sharp instruments. Parents are afraid to take their children to visit the dentist because it will affect the child’s oral and dental health. The aim of this study was to examine the relationship between parents’ knowledge, attitudes and practices regarding children’s dental care visits during the Covid-19 pandemic and parents’ age and education level. Descriptive research with a cross-sectional design. The research subjects were 106 parents of children aged 6-12 years. Sampling was taken using the interview method with 11 questions. Analysis using Chi square. Research results: 26.4% of parents from the 30-39 year age group stated that dental care could cause children to be infected with the Covid-19 virus (p<0.05), based on the level of knowledge, parents with a postgraduate level of knowledge answered that dental care could cause 19.8% of children were infected with the Covid virus (p<0.05). There were no differences in parental attitudes based on age and parental education level in taking their children to the dentist (p>0.05). It was concluded that there was no relationship between age and parents’ level of knowledge regarding children’s dental care visits during the Covid-19 pandemic.